Novel Nucleic Acid-Based Agents: siRNAs and miRNAs - Pereira, Tiago C.; Lopes-Cendes, Iscia (Central Nervous System Agents in Medicinal Chemistry, 2008)
A novel class of therapeutic agents based on nucleic acids has emerged and shown very promising pre-clinical results, named small interfering RNAs (siRNAs) and microRNAs (miRNAs). siRNAs are small RNA duplexes capable of silencing undesired (i.e., mutant, exogenous or aberrant) gene expression with high specificity through a mechanism known as RNA interference. These agents have called special attention to neuroscience since they have been used to experimentally treat a variety of neurological diseases with distinct etiologies such as viral, prions, genetic disorders and others. siRNAs have also been used in other scenarios as: drug-receptor blockage, inhibition of pain signaling and regulation of behavior. Although in a very initial stage, miRNAs also promise novel therapeutic approaches. In this review article we intend to introduce clinicians and researchers to the novel field of si- and miRNA-mediated gene silencing strategies, its history, use in cell and animal models, delivery methods, current status and possible applications in future clinical practice.